International Water Scarcity and Variability : Managing Resource Use Across Political Boundaries - Dinar, Shlomi; Dinar, Ariel, 1947- (Book collections on Project MUSE., 2017)
"International Water Scarcity and Variability considers international water management challenges created by water scarcity and environmental change. Although media coverage and some scholarship tend to cast natural resource shortages as leading inexorably toward war, Shlomi Dinar and Ariel Dinar prove that there are many examples of and mechanisms for more peaceful dispute resolution regarding natural resources, even in the face of water paucity and climate change. The authors base these arguments on both global empirical analyses and case studies. Using numerous examples that focus on North America, Europe, Central Asia, and the Middle East, this book asks scholars and policy makers to consider strategies and incentives to help lessen conflict and motivate cooperation under scarcity and increased variability of water resources"--Provided by publisher.